London dispersion forces in molecules, solids and nano-structures : an introduction to physical models and computational methods /: an introduction to physical models and computational methods. ([2020]) - Ángyán, János, 1956-; Dobson, John; Jansen, Georg; Gould, Tim
No abstract available